Smart Village: Mobile-Based Community Reporting Application - Anggara, Muhammad Reza; Kurniawan, Didik; Ardiansyah, Ardiansyah; Irawati, Anie Rose (International Journal of Electronics and Communications Systems, 2022)
Smart Village innovatively uses information technology to improve quality of life and efficiency. This study seeks to cover research gaps, contribute to the research field, and serve as a platform for primary probabilistic research by overcoming a proposed concept about The Community Reporting application as a solution for mobile phones. This application development uses the DART language with the Flutter Framework. The research stages are divided into four parts: problem analysis, literature study, system development, and report writing. The UAT test on the community reporting application got a score of 81.43 percent from community respondents. Furthermore, the community reporting administration system scored 88.3% of the village apparatus respondents. Therefore, the developed application could be well received. The government and community should contribute to implementing government and developing villages based on information technology.